2022
DOI: 10.1002/ijgo.14333
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine see‐saw across pregnancy, its related complexities and consequences

Abstract: Pregnancy can be compared to an organ transplant in immunology and the immune system. The fetus is "semiallogeneic" because of the presence of antigens originating from both mother and father.Throughout pregnancy, the fetus in the uterus can set off an immune response, yet the mother's immune system does not reject it. In layman's terms, the immune system of a pregnant woman is responsible for protecting the fetus from pathogens. It should tolerate the semiallogeneic fetus despite the presence of paternal allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 97 publications
0
6
0
Order By: Relevance
“…IL-10, etc.) are also increased to prevent excessive inflammatory responses ( 20 ). It has been shown that inflammatory cytokines/chemokines are significantly dysregulated in mothers infected with SARS-CoV-2 prior to delivery, but uninfected pregnant controls may also exhibit a large degree of variability in their cytokine/chemokine levels ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…IL-10, etc.) are also increased to prevent excessive inflammatory responses ( 20 ). It has been shown that inflammatory cytokines/chemokines are significantly dysregulated in mothers infected with SARS-CoV-2 prior to delivery, but uninfected pregnant controls may also exhibit a large degree of variability in their cytokine/chemokine levels ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the increase of pro-inflammatory cytokines, we also found increase of anti-inflammatory cytokines; perhaps as an attempt to contain the local inflammatory process without threatening the pregnancy. Anti-inflammatory cytokines such as IL-10 and transforming growth factor (TGF-β) are typically increased primarily in the second trimester, and decrease during the first and third trimesters ( Bränn et al, 2019 ; Meyyazhagan et al, 2022 ). For the two cytokines we noted statistical difference between controls and cases.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of cytokines as critical mediators in the inflammatory process that triggering labor has been demonstrated [ 21 ], very few predictive models consider their measurement in the PB screening process [ 22 , 23 , 24 ]. However, none have been implemented in clinical practice.…”
Section: Introductionmentioning
confidence: 99%